Public debt management : theory and application - Omoruyi, Samuel Edorisiagbon; West African Institute for Financial and Economic Management (Lagos, Nigeria West African Institute for Financial and Economic Management, University of Lagos Press and Bookshop, 2016)
The book offers a unique view of the subject from the perspective of a practitioner and econometrician. The mainstream analysis in the book focuses on theories, principles and issues of public debt sustainability.
Includes bibliographical references and index.
oif 06/12/2017
Loans
Keywords: Debts, Public